Ammonium zincates as suitable catalyst for the room temperature cycloaddition of CO2 to epoxides - Panza, Nicola; Alberti, Matteo; Damiano, Caterina; Caselli, Alessandro (Frontiers in Catalysis, 2022)
We have recently shown that simple ammonium ferrates are competent catalyst for the cycloaddition reaction of CO2 to epoxides under moderate reaction conditions (T = 100 °C, P(CO2) = 0.8 MPa). We report here that ammonium zincates of general formulae [TBA]2[ZnX4] (TBA = tetrabutylammonium), simply obtained by treating an ethanolic solution of an appropriate zinc(II) salt with two equivalents of tetrabutylammonium halides, outperform ammonium ferrates in the synthesis of cyclic carbonates under milder reaction conditions (room temperature and atmospheric CO2 pressure). Using [TBA]2[ZnBr4] complex as homogeneous catalyst at 100 °C and P(CO2) = 0.8 MPa a 52% conversion of styrene oxide with complete selectivity in styrene carbonate in just 15 min was observed, corresponding to a Turnover frequency (TOF) of 416 h-1. The same catalyst proved to be very active even at room temperature and atmospheric or very moderate CO2 pressures (0.2 MPa), with a quite broad range of substrates, especially in the case of terminal epoxides, with high selectivity towards cyclic carbonate products. The difference in reactivity of terminal and internal epoxides could be exploited using 4-vinylcyclohexene dioxide, where the endocyclic epoxide remained untouched when reacted at room temperature and the formation of the di-carbonate product was observed only at harsher conditions. A multigram scale conversion of propylene oxide was achieved (46 mmol) and the catalyst also proved to be recyclable (3 cycles) by distillation of the product and subsequent addition of fresh reagent, maintaining high conversion values and complete selectivity for propylene carbonate. This simple zinc-based catalytic system, which outperform the recently reported iron-based one by working at much milder conditions, could represent a valuable prospect in both laboratory and industrial scale, combining an inherent cheapness and synthetic easiness that should be deeply considered when the goal is to give value to a waste product as CO2.